Influence of Covid-19 Pandemic Disease on Educational Scheme as Express by Undergraduates - Ibrahim ologele (IJORER : International Journal of Recent Educational Research, 2022)
The Covid-19 pandemic disease has modified the education system in Nigeria to distance learning using online platforms to stop and reduce the chain of distribution of coronavirus which highly contagious disease among students. This study objectives are to investigate whether Covid-19 pandemic result to; (1) change in university academic calendar, (2) difficulty in coping with online class, (3) inability to concentrate with online education tools. The population of the study comprised all undergraduates in the Faculty of Education, University of Ilorin, Nigeria. The study adopted a descriptive research design of survey type which involved the use of three-stages sampling techniques to choose two hundred and fifty-seven undergraduates from the five selected departments out of nine departments in the study area. The researcher developed a questionnaire validated by three experts in the related field was used as an instrument for the study. The findings of the study indicated that the Covid-19 pandemic disease has influence on changes in University academic calendar, has influence on the difficulty in coping with online class and also, has influence on inability to concentrate with online educational tools among Undergraduates. The researcher recommends among others that the lecturers should use appropriate techniques and teaching aids that will make online lessons interesting for learners